Reaction of differential wheat and triticale genotypes to natural stripe rust [Puccinia striiformis f. sp. tritici] infection in Saskatchewan, Canada. Issue 2 (3rd April 2017) - Brar, Gurcharn S.; Graf, Robert; Knox, Ron; Campbell, Heather; Kutcher, H.R.
Abstract: Stripe rust of wheat ( Triticum spp. L.) is an emerging problem in western Canada. The causal pathogen ( Puccinia striiformis f. sp. tritici Eriks.) has the potential to overwinter, which is a concern because of green bridging leading to earlier establishment of rust epidemics. Resistance conferred by seedling/all-stage and adult plant genes is the most effective approach to manage this disease. However, many Canadian wheat varieties lack seedling or all-stage resistance. The effectiveness of Yr genes under field conditions was assessed by exposing differentials/varieties carrying Yr genes to natural inoculum in multiple environments. The differentials were planted at multiple Saskatchewan locations in 2013, 2014 and 2016 and significant stripe rust was detected at 12 site-years. Additionally, 33 winter wheat varieties and advanced breeding lines were assessed for stripe rust reaction in 2016 at Swift Current, Saskatchewan. Disease severity was assessed on flag and penultimate leaves between early milk to soft dough growth stages. The genes Yr5, Yr15, YrSP and those in 'Yamhill' are effective in Saskatchewan under field conditions. Genes/differentials were classified into two major groups based on cluster analysis, one with defeated genes and the other with partial resistant genes. Genes YrA, Yr6, Yr7, Yr8, Yr9, Yr27, Yr29, Yr31, Yr32 and YrSu were not effective in the field to SK races. At Swift Current, winter wheat varieties/lines carrying Yr17 were resistant in the field, whereas those carrying Yr10 were not.